A case study of pre-requirements specification traceability practices in a retail environment - Williams, Jeandre Charisse (Department of Construction Economics and Management, 2015)
Purpose: An exploration into the application of pre-requirements specification traceability (pre-RST) practices in Information Systems (IS) projects within a retail setting. Research Design/methodology: A qualitative study in the interpretivist tradition applied within a single case study setting was selected. Findings: Awareness and value-perception emerged as the most significant challenge to overcome with recommendations for a well-considered organisational change management programme to address this. The potential impact on the trust relationship amongst requirements practitioners and participants is a factor to be addressed. More readily accessible requirements engineering guides that include pre-RST as a prominent aspect is required to raise awareness levels amongst practitioners. Practical implications: The research points to a need to raise awareness amongst practitioners through improved and more readily accessible requirements engineering guides that include pre-RST as a prominent aspect. It also highlights what to consider when embarking upon pre-RST, most prominently the need for carefully considered change management programme to tackle value-perception. Originality/value: Addressing the paucity in case study insights, this research provides an understanding of practice, awareness, value-perception and perceived challenges to pre-RST. Considerations for pre-RST implementation, including careful consideration for the trust relationship amongst requirements practitioners and participants is highlighted. Limitations: The case study was limited to eleven interviews in the retail industry and therefore may not be generalisable to other industries or general practice.